2021
DOI: 10.1070/sm9446
|View full text |Cite
|
Sign up to set email alerts
|

Singularities on toric fibrations

Abstract: In this paper we investigate singularities on toric fibrations. In this context we study a conjecture of Shokurov (a special case of which is due to M Kernan which roughly says that if is an -lc Fano-type log Calabi-Yau fibration, then the singularities of the log base … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Hence Conjecture 1.5 under assumption (2') holds when the coefficients of B| F are bounded from below away from zero as a consequence of the Borisov-Alexeev-Borisov conjecture proved by Birkar [Bir19,Bir21]. Very recently, Birkar and Y. Chen [BC21] proved Conjecture 1.5 under assumption (2') for toric morphisms between toric varieties. We refer the readers to [Bir18, Theorems 1.9 and 2.5] for more related results.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Hence Conjecture 1.5 under assumption (2') holds when the coefficients of B| F are bounded from below away from zero as a consequence of the Borisov-Alexeev-Borisov conjecture proved by Birkar [Bir19,Bir21]. Very recently, Birkar and Y. Chen [BC21] proved Conjecture 1.5 under assumption (2') for toric morphisms between toric varieties. We refer the readers to [Bir18, Theorems 1.9 and 2.5] for more related results.…”
Section: Introductionmentioning
confidence: 86%
“…The bounds in Theorem 1.10 are optimal by Example 4.1. Y. Chen informed us that together with Birkar, they also got the lower bound 1 2 in Theorem 1.10 for toric morphisms between toric varieties in an earlier version of [BC21]. As a related result, when dim X − dim Z = 2, Mori and Prokhorov [MP09] showed that any 3dimensional terminal del Pezzo fibration has no fibers of multiplicity > 6.…”
Section: Introductionmentioning
confidence: 87%
“…Hence, under assumption (2’), Conjecture 1.5 holds when the coefficients of are bounded from below away from zero as a consequence of the Borisov–Alexeev–Borisov conjecture proved by Birkar [7, 8]. Very recently, Birkar and Y. Chen [10] proved Conjecture 1.5 under assumption (2’) for toric morphisms between toric varieties. We refer the reader to [6, Theorems 1.9 and 2.5] for more related results. Following ideas in [5], it is indicated by [11, Proposition 7.6] (see [13, Theorem 1.10] for an embryonic form) that Conjecture 1.5 might be a consequence of Shokurov’s -lc complements conjecture.…”
Section: Introductionmentioning
confidence: 90%
“…Hence, under assumption (2’), Conjecture 1.5 holds when the coefficients of are bounded from below away from zero as a consequence of the Borisov–Alexeev–Borisov conjecture proved by Birkar [7, 8]. Very recently, Birkar and Y. Chen [10] proved Conjecture 1.5 under assumption (2’) for toric morphisms between toric varieties. We refer the reader to [6, Theorems 1.9 and 2.5] for more related results.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation